Sanctions, sales, and stigma: intermediary online firms' market role in sustaining trade - Avdeenko, Alexandra; Kaiser, Maximilian; Kis-Katos, Krisztina; Reher, Leonie (Journal of international economics, 2026)
In the wake of Russia’s full-scale invasion of Ukraine in February 2022, online intermediaries enabled brands to retain a presence in the Russian market as many global companies—presumably or actually—withdrew due to legal and reputational concerns. This paper examines how sales by intermediaries responded to international sanctions. Using novel data on customer transactions of 95 global brands from 1761 web shops, we show that sales to Russia dropped significantly after the invasion, especially among shops from countries enacting export restrictions. This drop was substantial yet not absolute. Guided by a stylized conceptual framework, we explore which intermediary shops helped sustain sales to Russia, linking their actions to economic incentives and the brand-specific legal and reputational concerns. Overall, we demonstrate how market structure shapes shops’ compliance with sanctions and highlight how economic incentives undermine compliance.